Pengaruh Penggunaan Media Papan Multi Fungsi Terhadap Hasil Belajar Matematika Siswa Kelas IV SD Negeri 104186 Tanjung Selamat Medan - Tarida Herawati Lumban Gaol; Reflina Sinaga; Anton Sitepu; Juliana Juliana; Saut Mahulae; Rumiris Lumban Gaol (Departement of Mathematics Education, 2023)
The purpose of this study was to determine whether there is an effect of using multifunctional board media on student learning outcomes in mathematics learning on KPK and FPB material for grade IV students of SD Negeri 104186 Tanjung Selamat. Through this study, a correlation coefficient of 0.989 was obtained with a significance level of 5% with the number of respondents (N) of 30 students, with an rtable of 0.361. So it can be concluded that there is a relationship between the two variables where rcount> rtable (0.989> 0.361). Based on the calculation results, the significance result is 0.000 <0.05, it can be concluded that the two variables have a relationship. In addition, to find out whether the two variables have a relationship, a comparison can be made between rcount and rtable. If rcount> rtable then the two variables have a relationship. With the number of respondents (N) as many as 30 students, the rtable is 0.361. While the rcount in the table above is 0.990. Because 0.990> 0.361, there is an influence between the multi-fungal board media on the learning outcomes of fourth grade students at SD Negegi 104186 Tanjung Selamat Medan. The calculation results of the influence of the two variables are shown with a correlation value of 0.990. Based on the interpretation table of r values, the correlation obtained lies in the range of r values 0.800-1.000, it can be concluded that the level of influence between variable X multi-function board media on variable Y student learning outcomes has a very high influence.